The effectiveness of proposed training program for small sided games in developing the accuracy passing ( Medium) of football players (under 15 years old - Nasri , Salah Eddine; Assam , Samir (sports creativity, 2025)
This study aimed to try to identify the effectiveness of training program proposed by small sided games in development of pass accuracy (Medium) in football players under 15 years of age, and from the field side and systematic, the study was conducted on the players of the Clubs of the regional league of Constantine (group B) and who represent the research community, and the simple was chosen in the method intent, which was represented by the club of (ESS) as an experimental sample and the club of the union of sétif, (USMS) as an officer sample, as well as the experimental method, and as a tool for the was used the test of the skill of pass accuracy (medium ) and this after subjecting it to scientific conditions, and from the statistical side was used the program of statistical package (spss) to process and analyze the data, and the results of the study resulted in the effectiveness of training by small